Evidence of support used for drug treatments in pediatric cardiology. Issue 2 (11th May 2021) - Back, Julia; Wåhlander, Håkan; Hanseus, Katarina; Bergman, Gunnar; Naumburg, Estelle
Abstract: Background and aims: Clinical support systems are widely used in pediatric care. The aim of this study was to assess the support for drug treatments used at pediatric cardiac wards and intensive care units in Sweden. Methods: Drug information, such as type of drug, indication, dose, and route of administration, for all in‐hospital pediatric cardiac patients, was included in the study. Treatments were classified as either on‐label (based on product information) or off‐label. Support for off‐label treatment was stratified by the use of clinical support systems (the national database on drugs, local, or other clinical experience guidelines). Results: In all, 28 patients were included in the study. The total number of drug treatments was 233, encompassing 65 different drugs. Overall, 175 (75%) treatments were off‐label. A majority of off‐label drug treatments were supported by other sources of information shared by experts. A total of 7% of the drug treatments were used without support. Conclusion: Off‐label drug treatment is still common in Swedish pediatric cardiac care. However, the majority of treatments were supported by the experience shared in clinical support systems. Key Points: Seventy‐five percent of all prescriptions in pediatric cardiology care were off‐label. A majority of patients received three or more drug treatments off‐label. Use of clinical support systems and guidelines was common, but in 7% of all drug treatments, no support was found for the chosen treatment. Abstract : This study assess the support for drug treatments used at paediatric cardiac. Seventy‐five percent of all prescriptions in paediatric cardiology care were off‐label. A majority of patients received three or more drug treatments off‐label. Use of clinical support systems and guidelines was common, but in 7% of all drug treatments, no support was found for the chosen treatment.